Implementation of Brand Promotion Strategy of the Faculty of Education, State University of Malang - Budi, Mochamad Eko; Adi, Eka Pramono; Setiyowati, Arbin Janu (Proceedings Series of Educational Studies, 2024)
This research explores the branding strategy implemented by the Faculty of Education (FIP) of State University of Malang (UM) to build a strong image and reputation among prospective students, the community, and industry. In the current era of digitalisation, an effective branding strategy is very important for educational institutions to attract public attention and increase trust. FIP UM uses the tagline ‘FIP ASIEK’ (Active, Smart, Innovative, Educative, Creative) as an effort to form positive perceptions and increase attractiveness. This research uses an observational approach with several stages, including literature observation, field observation, benchmarking, brainstorming, and visual design. Data were collected from various sources such as the vision, mission, and characteristics of FIP UM consumers, as well as brand identity models from local and national campuses. The results show that the branding of FIP UM through the tagline ‘FIP ASIEK’ packages the values conveyed by the faculty among the community. The branding strategy implemented is not only through digital media and mass media, but also through merchandise products designed to strengthen the identity and core values of the faculty. This strategy is considered successful in building a positive image that is relevant to today's technological developments. In conclusion, a holistic and sustainable branding strategy is needed to maintain the competitive position of FIP UM in the world of higher education. Keywords: Branding Strategy; FIP UM; Brand Promotion